PENGEMBANGAN WEB SISTEM INFORMASI PERPUSTAKAAN MENGGUNAKAN SLIMS DAN WHATSAPP GATEWAY DI SMK NEGERI 40 JAKARTA: Development Of Library Information System Web Using SLiMS And WhatsApp Gateway At SMK Negeri 40 Jakarta - Septia Dwi Handayani; Widodo Widodo; Z.E. Ferdi Fauzan Putra (LPPM Universitas Abdurrab, 2024)
The SMKN 40 Jakarta library had service and administrative processing problems, namely difficulty reading manual administrative data collection writing, library members lack information on book stock availability, and delays in returning books. Therefore, this researched aims to develop a web-based library information system used SLiMS and adding notification features with WhatsApp gateway to whacenter api endpoint. This researched used Rapid Application Development for software development method. Based on the results of system testing carried out used Black Box State Transition Testing, it was 100% successful meaning that website could function properly. Testing continued with System Usability Scale (SUS) from 75 student respondents, teachers and librarians which resulted in a score of 62,3. A valued of 62,3 was interpreted as meaning that system had marginally low Acceptability Ranges, Grade Scale D, and Adjective Ratings